Effect of HFE Gene Mutations on Iron Metabolism of Beta-Thalassemia Carriers - Mónaco, María Elvira (2023)
The human hemochromatosis protein HFE is encoded by the HFE gene and participatesin iron regulation. The aim of this study was to detect the most frequent HFE gene mutations in acontrol population and in β-thalassemia trait (BTT) carriers, and to study their relationship with ironmetabolism. Total blood count, hemoglobin electrophoresis at alkaline pH, HbA2 quantification, iron(Fe), total Fe binding capacity and ferritin were assayed. HFE gene mutations were analyzed by realtime PCR. A total of 119 individuals (69 normal and 50 BTT) were examined. In the control group, 9% (6/69) presented a codon 282 heterozygous mutation (C282Y), and 19% a codon 63 mutation (H63D) (13/69, 11 heterozygotes and 2 homozygotes). In the BTT group, 3 carriers (6%) were heterozygous for C282Y, 14 (28%) for H63D, 1 (2%) for a codon 65 mutation and 1 (2%) was H63D and C282Y d oubleheterozygous. Control group Fe metabolism did not show significant differences (p > 0.05) according to whether or not they carried an HFE gene mutation; while the BTT group with and without HFE mutation showed higher Fe and ferritin than the control group (p < 0.05). However, no increases in iron parameters were detected in BTT carriers that simultaneously exhibited an H63D mutation compared to BTT subjects without a mutation. Therefore, the iron metabolism alterations observed in BTT carriers could not be attributed to the presence of HFE gene mutations. It is likely that BTT individuals have other genetic modifiers that affect their iron balance.